1996
DOI: 10.1111/j.1432-1033.1996.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

NMR Data Show that the Carcinogen N‐2‐Acetylaminofluorene Stabilises an Intermediate of −2 Frameshift Mutagenesis in a Region of High Mutation Frequency

Abstract: The heteroduplex, d(ACCGGCGCCACA) . d(TGTGG-CCGGT), containing two bulged bases, a cytosine and the guanine G7, either unmodified or modified with the carcinogen N-2-acetylaminofluorene, have been studied by NMR as models of slipped-mutagenic intermediates (SMI). The melting temperature of the modified heteroduplex is strongly increased compared with that of the unmodified heteroduplex. NMR studies have shown that all the bases of the unmodified heteroduplex are stacked within the helix, without any disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 20 publications
2
74
0
Order By: Relevance
“…As a result, the 5Ј-G AAF pC dinucleotide in the template strand remains unpaired. We have previously shown that the G-AAF adduct stabilizes such a slipped structure by virtue of stacking interactions between the aromatic AAF moiety with the adjacent bases (33)(34)(35). We suggest that the LT can adopt two conformations.…”
Section: Characterization Of the Frameshift Replication Intermediate mentioning
confidence: 99%
“…As a result, the 5Ј-G AAF pC dinucleotide in the template strand remains unpaired. We have previously shown that the G-AAF adduct stabilizes such a slipped structure by virtue of stacking interactions between the aromatic AAF moiety with the adjacent bases (33)(34)(35). We suggest that the LT can adopt two conformations.…”
Section: Characterization Of the Frameshift Replication Intermediate mentioning
confidence: 99%
“…However, the molecular understanding of how they exert mutation in vivo is generally poor and is complicated by adduct-induced conformational heterogeneities. The AAF-adduct exists predominantly in the base-displaced "stacked" (S) conformation (9)(10)(11). Because it lacks Watson-Crick base pairs at the lesion site, the AAF-adduct produces a major structural distortion in DNA.…”
Section: And N-(2′-deoxyguanosin-8-yl)-2-aminofluorene (Af)mentioning
confidence: 99%
“…To simulate the two-base slippage product, Fuchs and Romano independently examined the thermal stability of an oligonucleotide duplex in which the GpC nucleotides opposite the C8-AAF adduct were deleted (41,46). The C8-AAF adduct at the G 3 -position was found to stabilize the duplex relative to the unmodified oligonucleotide by 15 °C.…”
Section: Thermal Melting (T M ) Studies Of Iq-adducted Oligo-nucleotidesmentioning
confidence: 99%